A study on Educating through Media in Islamic Education Perspective in Higher Education in Pakistan - Asif Nadeem , Muhammad; Qazi, Sana; Azhar, Sania; Badar Habib, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Advances in science and technology are motivating the teachers to use technology in the teaching process. Teaching through media technology seemed to enhance capabilities among learners. The educational media used should be adapted to the development and demands of the times. Using the right educational media in the process of learning to teach will make it easier to attain learning goals. The purpose of this article is to describe modern educational media used in this technological age and compare them with those that were used in the Islamic education system since the initial days of the spread of the religion Islam. The research method used in this discussion is descriptive. The result attained from this discussion seemed to identify that in the early days of the spread of Islam, the educational media was used for the enhancement of teaching and the teaching process, and these technological media were used by the Messenger of Allah, the Holy Prophet Muhammad. الله یلص ہیلع (ملسو ہلآ وThe Holy Prophet Muhammad) الله یلص ہیلع (ملسو ہلآ وused media while teaching the knowledge and rules of Islamic religion to theholy companions )  ( . ہیلعہللا ناوضر In addition, in the hadith ) (ہکرابم تیدحthere are several terms used to indicatethe use of educational media in learning, such as pictures, gravel, and fingers and hands. The conclusion of this article is that the educational media seemed to influence learning aptitude of the learners. The use of media technology appeared to be inevitable for complete and accurate learning process. Media is an impactful and credible learning source of information to get the end result in the learning process.